Skrinning Resep Interaksi Obat Pasien Hipertensi dan Gagal Ginjal Periode Oktober S.d Desember 2023 di Rumah Sakit Rasyida Medan - Sri Devi Alfitriani; Novitaria Br Sembiring; Asyrun Alkhairi Lubis; Nurasni Nurasni (Pusat Riset dan Inovasi Nasional, 2025)
Hypertension is a significant health issue in Indonesia, frequently referred to as a silent killer due to its asymptomatic nature. Hypertension complications may result in damage to essential organs, including the heart, brain, and kidneys, potentially culminating in chronic kidney failure (CKD). The therapy of hypertension and renal failure requires appropriate pharmacological intervention to avert complications and enhance patient quality of life. This research seeks to identify medications often prescribed to patients with hypertension and renal failure, ascertain the prevalence of concurrent illnesses, and assess potential drug interactions in prescriptions at Rasyida Hospital Medan from October to December 2023. The research used a descriptive methodology via an analysis of patient prescriptions. The study's findings indicated the use of diverse combinations of antihypertensive medications and renal failure treatment, along with the possibility of drug interactions in multiple patient prescriptions. The results underscore the need of prescription screening and monitoring for drug interactions within clinical pharmacy services to mitigate the risk of medication mistakes and enhance the safety and efficacy of treatment in patients with hypertension and renal failure.